Composition and abundance of zooplankton community of an impacted estuarine lagoon in Northeast Brazil - Almeida, LR; Costa, IS; Eskinazi-Sant'Anna, EM (Brazilian journal of biology, 2012)
Guaraíras Lagoon is a shallow coastal lagoon subject to intense human impacts, including shrimp aquaculture, urban expansion and agricultural activities, and is therefore vulnerable to eutrophication. With the aim of detecting the effects of human-mediated disturbance and environmental change in the lagoon, a spatial-temporal study was conducted in order to assess the actual ecological status of the lagoon and the species composition and density of the mesozooplankton, highlighting copepod assemblages. Algal biomass (chlorophyll-a) and total phosphorus concentration indicated that the lagoon is a meso-eutrophic coastal system in the inner part, and is oligotrophic in the areas influenced by the marine waters. High salinities were recorded in the lagoon, characterizing the lagoon as a coastal-marine ecosystem, rather than true estuarine. Mesozooplankton abundance fluctuated widely and showed marked spatial heterogeneity. The copepod assemblage was characterized by a coastal/estuarine group dominated by Oithona spp., Acartia lilljeborgi and Parvocalanus crassirostris in the inner areas of the lagoon, and a marine group characterized by the copepods Paracalanus quasimodo, Calanopia americana, Corycaeus (C.) speciosus and Monstrilloida in the area of marine influence. Thus, the spatial variability in the distribution of mesozooplankton species can be ascribed to the presence of a horizontal gradient of salinity and trophic conditions. Overall, the results showed that spatial variation in the water physicochemical characteristics of Guarairas Lagoon have significant effects on the structure and repartition of the mesozooplankton assemblages, which may potentially affect the functioning and biodiversity of this coastal ecosystem. A laguna de Guaraíras é uma laguna costeira rasa sujeita a intensos impactos humanos, incluindo a carcinocultura, expansão urbana e agricultura, e desta forma, sujeita à eutrofização. Um estudo espaço-temporal foi conduzido com o objetivo de avaliar o status ecológico da laguna e a composição de espécies e densidade do mesozooplâncton, com destaque para a assembleia de copépodos. A biomassa algal (clorofila-a) e a concentração de fósforo total indicaram que a laguna apresenta condições mesoeutróficas em sua porção interna, e oligotróficas nas áreas sob influência marinha. Foram registradas altas salinidades na laguna, caracterizando a laguna como um sistema costeiro-marinho, ao invés de um ambiente verdadeiramente estuarino. A abundância zooplanctônica flutuou expressivamente, e apresentou uma marcada heterogeneidade espacial. A assembleia de copépodos foi caracterizada por um grupo costeiro-estuarino, dominado por Oithona spp., Acartia lilljeborgi e Parvocalanus crassirostris nas áreas interiores da laguna, e um grupo marinho caracterizado pelos copépodos Paracalanus quasimodo, Calanopia americana, Corycaeus (C.) speciosus e Monstrilloida na área sob influência marinha. Desta forma, a variabilidade espacial na distribuição das espécies zooplanctônicas pode ser atribuída à presença de um gradiente horizontal de salinidade e condições tróficas. De uma forma geral, os resultados mostraram que a variação espacial nas características físicas e químicas da laguna de Guaraíras tem efeitos significativos sobre a estrutura e composição das assembleias zooplanctônicas, as quais podem afetar potencialmente o funcionamento e a biodiversidade deste ecossistema costeiro.